Inter‐Flake Quantum Transport of Electrons and Holes in Inkjet‐Printed Graphene Devices. (26th October 2020) - Wang, Feiran; Gosling, Jonathan H.; Trindade, Gustavo F.; Rance, Graham A.; Makarovsky, Oleg; Cottam, Nathan D.; Kudrynskyi, Zakhar; Balanov, Alexander G.; Greenaway, Mark T.; Wildman, Ricky D.; Hague, Richard; Tuck, Christopher; et al.
Abstract: 2D materials have unique structural and electronic properties with potential for transformative device applications. However, such devices are usually bespoke structures made by sequential deposition of exfoliated 2D layers. There is a need for scalable manufacturing techniques capable of producing high‐quality large‐area devices comprising multiple 2D materials. Additive manufacturing with inks containing 2D material flakes is a promising solution. Inkjet‐printed devices incorporating 2D materials have been demonstrated, however there is a need for greater understanding of quantum transport phenomena as well as their structural properties. Experimental and theoretical studies of inkjet‐printed graphene structures are presented. Detailed electrical and structural characterization is reported and explained by comparison with transport modeling that include inter‐flake quantum tunneling transport and percolation dynamics. The results reveal that the electrical properties are strongly influenced by the flakes packing fraction and by complex meandering electron trajectories, which traverse several printed layers. Controlling these trajectories is essential for printing high‐quality devices that exploit the properties of 2D materials. Inkjet‐printed graphene is used to make a field effect transistor and Ohmic contacts on an InSe phototransistor. This is the first time that inkjet‐printed graphene has successfully replaced single layer graphene as a contact material for 2D metal chalcogenides. Abstract : Experimental and theoretical studies of inkjet‐printed graphene reveal that the electrical properties are strongly influenced by the flakes packing fraction and by complex meandering electron trajectories. Charge transport is modeled by inter‐flake quantum tunneling and percolation dynamics, which explain the properties of inkjet‐printed graphene as an active channel in a field effect transistor and as high‐quality Ohmic contacts in InSe phototransistors.